2016
DOI: 10.3233/dev-16194
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Early Attachment Mechanisms Contribute to Attachment Quality: Case Studies Including Babies Born Preterm

Abstract: Three boys (an extremely preterm, a moderate preterm twin and a full-term toddler; all 12 to 15 months old) were selected from a large sample to investigate mechanisms of parent-child attachments, specifically of babies born preterm. Attachments were observed at home with the Attachment-Q-Sort (AQS) as well as in the lab with the Strange Situation (SS). Both AQS and SS were used twice for each boy, separately with his mother and father. Whereas the SS was efficient in analyzing basic attachment repertoire, lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Former studies of mother-child attachment in children born before term have not integrated all these factors. Furthermore, (2) the AQS was employed instead of the traditional Strange Situation Procedure, which has been questioned in its use for children born preterm since they are particularly vulnerable to stress [ 5 , 55 ]. (3) We also investigated mother-child and father-child attachment, while most previous studies focused exclusively on mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies of mother-child attachment in children born before term have not integrated all these factors. Furthermore, (2) the AQS was employed instead of the traditional Strange Situation Procedure, which has been questioned in its use for children born preterm since they are particularly vulnerable to stress [ 5 , 55 ]. (3) We also investigated mother-child and father-child attachment, while most previous studies focused exclusively on mothers.…”
Section: Discussionmentioning
confidence: 99%
“…While some U n c o r r e c t e d A u t h o r P r o o f R. Kissgen et al / Infant-Father Attachment in Infants Born Preterm studies found no differences in the infant-mother attachment between infants born preterm and infants born at term (Karabekiroglu et al, 2015;Korja et al, 2012), other studies report significantly more attachment disorganisation (Wolke et al, 2014), or overall to a lesser extent attachment security (Mangelsdorf et al, 1996) in preterm infants. Although fathers have been included in the care of their preterm infants during their stay in hospital on an increasingly broader base for several years now, they have thus far been relegated to a secondary role in attachment research (Deeney et al, 2009;Kißgen & Carlitscheck, 2013;Witting et al, 2016). Investigating infant-father attachment and its contribution to the development of children from high-risk groups may, however, provide valuable insights, just as the secure infant-mother attachment has been found to be a strong protecting factor in child development (Belsky & Fearon, 2002;Rutter, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…So far there have only been three studies investigating the influence of preterm birth on infant-father attachment (Easterbrooks, 1989;Ruiz et al, 2018;Witting et al, 2016). As early as 1989, using the Strange Situation Procedure (SSP) (Ainsworth et al, 1978), Easterbrooks found that preterm birth did not influence infant-father attachment, infant-mother attachment, and temporal stability of attachment (13 and 20 months), nor did it create any difference in the attachment to the mother or the father.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation